Platform Inovatif Bagi UMKM Pasca Pandemi Covid-19 UMKM, Industri, Dan Ekonomi Kreatif - Putri, Yustika Kusuma (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2023)
Covid-19 is an unpredictable event that impacts the economic sector. Micro, Small and Medium Enterprises (MSMEs) play a major role in the Indonesian economy. However, of the 59.9 million MSMEs in Indonesia, the success rate of selling products through digital platforms is only 4%. The obstacles commonly encountered by MSMEs are the lack of knowledge of running an online business as much as and the unpreparedness of workers to use the internet as much. Whereas online media provides a promising market. Therefore, the application